Influence Of Health Behaviour Factors On Basic Immunisation In Indonesia 2022 - Syifa Faikhatul Ilmi; Efri Diah Utami (Saintika Medika)
Background: The coverage of complete basic immunisation in Indonesia from 2020 to 2022 never reached the target of the 2020-2024 National Medium-Term Development Plan despite various efforts made by the government. As a result, there are many cases of infectious diseases in children. Therefore, this study aims to determine the overview of the coverage of complete basic immunisation in Indonesia in 2022 and the effect of antenatal care visits, doctor ratio, and ownership of immunisation documents on the coverage of complete basic immunisation in Indonesia in 2022.